Coronavirus Disease 2019 (COVID-19) in Americans Aboard the Diamond Princess Cruise Ship. (12th August 2020) - Plucinski, Mateusz M; Wallace, Megan; Uehara, Anna; Kurbatova, Ekaterina V; Tobolowsky, Farrell A; Schneider, Zachary D; Ishizumi, Atsuyoshi; Bozio, Catherine H; Kobayashi, Miwako; Toda, Mitsuru; Stewart, Andrea; Wagner, Riley L; et al.
Abstract: Background: The Diamond Princess cruise ship was the site of a large outbreak of coronavirus disease 2019 (COVID-19). Of 437 Americans and their travel companions on the ship, 114 (26%) tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods: We interviewed 229 American passengers and crew after disembarkation following a ship-based quarantine to identify risk factors for infection and characterize transmission onboard the ship. Results: The attack rate for passengers in single-person cabins or without infected cabinmates was 18% (58/329), compared with 63% (27/43) for those sharing a cabin with an asymptomatic infected cabinmate, and 81% (25/31) for those with a symptomatic infected cabinmate. Whole genome sequences from specimens from passengers who shared cabins clustered together. Of 66 SARS-CoV-2-positive American travelers with complete symptom information, 14 (21%) were asymptomatic while on the ship. Among SARS-CoV-2-positive Americans, 10 (9%) required intensive care, of whom 7 were ≥70 years. Conclusions: Our findings highlight the high risk of SARS-CoV-2 transmission on cruise ships. High rates of SARS-CoV-2 positivity in cabinmates of individuals with asymptomatic infections suggest that triage by symptom status in shared quarters is insufficient to halt transmission. A high rate of intensive care unit admission among older individuals complicates the prospect of future cruise travel during the pandemic, given typical cruise passenger demographics. The magnitude and severe outcomes of this outbreak were major factors contributing to the Centers for Disease Control and Prevention's decision to halt cruise ship travel in US waters in March 2020. Abstract : The Diamond Princess cruise ship was the site of a large outbreak of coronavirus disease 2019 (COVID-19). Our findings highlight the high risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission on cruise ships.